The Situation of Catholic Instruction in Transylvania during the Communist Takeover - László HOLLÓ (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2020)
In less than one year, the Catholic Church, just like the other denominations, lost its school network built along the centuries. This was the moment when the bishop wrote: “No one can resent if we shed tears over the loss of our schools and educational institutions”. Moreover, he stated that he would do everything to restore the injustice since they could not resent if we used all the legal possibilities and instruments to retrieve our schools that we were illegally dispossessed of. Furthermore, he evaluated the situation realistically and warned the families to be more responsible. He emphasized the parents’ responsibility. First and foremost, the mother was the child’s first teacher of religion. She taught him the first prayers; he heard about God, Jesus, the Virgin Mary, and the angels from his mother for the first time. He asked for the mothers’ and the parents’ support also in mastering the teachings of the faith. Earlier, he already instructed the priests to organize extramural biblical classes for the children and youth. At this point, he asked the families to cooperate effectively, especially to lead an ardent, exemplary religious life, so that the children would grow up in a religious and moral life according to God’s will, learning from the parents’ examples. And just as on many other occasions throughout history, the Catholic Church started building again. It did not build spectacular-looking churches and schools but rather modest catechism halls to bring communities together. These were the places where the priests of the dioceses led by the bishop’s ex-ample and assuming all the persecutions, incessantly educated the school children to the love of God and of their brethren, and the children even more zealously attended the catechism classes, ignoring their teachers’ prohibitions.